Surgery and Resource Utilization Trends for Pediatric Intussusception From 2005 Through 2014 - Bhatt, Parth (Cureus, 2020)
Background: Air or barium enema reduction is becoming increasingly common and safer for pediatric intussusception. However, little is known about trends of pediatric intussusception requiring surgical intervention in the United States.  Methods: National Inpatient Sample database was analyzed from 2005-2014 to identify pediatric (≤18 years) intussusceptions along with procedures such as enema and/or surgical intervention. Trends in the rates of surgical intervention were examined according to encounter-level (age, gender, race, comorbidities) and hospital-level (hospital census region, teaching status) characteristics. Outcomes of pediatric intussusception requiring surgical intervention were analyzed in terms of length of stay and cost of hospitalization. Factors associated with surgical intervention were also analyzed. P value of < 0.05 was considered significant.  Results: Out of 21,835 intussusception hospitalizations requiring enema or surgical intervention, 14,415 (66%) had surgical intervention; 90% of which (12,978) had no preceding enema. Surgical intervention rates among intussusception hospitalizations varied by age (highest < 1 year), gender (male > females) and race (Hispanics > Whites and Blacks). During the study period, overall surgical intervention rate remained stable (2.2 to 1.7, P=0.07) although it declined in those under 1 year of age. Children with severe disease, gastrointestinal comorbidities over the age of 4 years had increased odds of surgical intervention, whereas hospitalization in large and urban teaching hospitals had decreased odds of surgical intervention. Length of stay and hospital cost remained stable from 2005-2014. Conclusion: The rates of surgical intervention and resource utilization for pediatric intussusception remained stable from 2005-2014, however they declined significantly in infants. The proportion of intussusception hospitalization requiring surgery remains high and further studies are needed to explore the possible factors.